Effects of Tumor-Derived DNA on CXCL12-CXCR4 and CCL21-CCR7 Axes of Hepatocellular Carcinoma Cells and the Regulation of Sinomenine Hydrochloride - Shen, Conghuan; Li, Jianhua; Li, Ruidong; Ma, Zhenyu; Tao, Yifeng; Zhang, Quanbao; Wang, Zhengxin (Frontiers in Oncology, 2022)
Currently, chemokines and their receptors, CXCL12-CXCR4 and CCL21-CCR7 axes, are deemed as vital factors in the modulation of angiogenesis and are crucial for the growth and development of liver cancer. Tumor-derived DNA can be recognized by immune cells to induce an autoimmune response. In this study, we demonstrated the mechanism of tumor-derived DNA on the CXCL12-CXCR4 and CCL21-CCR7 axes of hepatocellular carcinoma cells and the regulatory effect of sinomenine hydrochloride. Tumor-derived DNA was separated from HCCLM cell lines. Tumor-derived DNA was transfected into SK-Hep1 cells by Lipofectamine 2000. We found that sinomenine hydrochloride reduced the expression of CXCR4, CXCR12, CCR7 and CCL21 in hepatocellular carcinoma cells, suppressed the growth and invasion of hepatocellular carcinoma cells, and increased apoptosis. In contrast to the controls, the protein expressions of CXCR4, CXCL12, CCR7, CCL21, P-ERK1/2, MMP-9 and MMP-2 in SK-Hep1 cells were significantly increased after transfection of tumor-derived DNA, while the increase was reversed by sinobine hydrochloride. Acid sinomenine interferes with tumor-derived DNA and affects ERK/MMP signaling via the CXCL12/CXCR4 axis in HCC cells. CXCR4 siRNA and CCR7 siRNA attenuated tumor-derived DNA activation of ERK1/2/MMP2/9 signaling pathways in HCC cells. CXCR4-oe and CCR7-OE enhance the stimulation of erK1/2 /MMP2/9 signaling pathway by tumor-derived DNA in HCC cells. Tumor-derived DNA reduced apoptosis and increased invasion of SK-Hep1 cells by CXCL12-CXCR4 axis and CCL21-CCR7 axis, and sinobine hydrochloride reversed this regulation. These results strongly suggest that tumor-derived DNA can increase the growth and invasion of oncocytes via the upregulation of the expression of CXCL12-CXCR4 and CCL21-CCR7 axis and through ERK1/2/MMP2/9 signaling pathway in HCC cells, and sinobine hydrochloride can inhibit this signaling pathway, thus inhibiting HCC cells. These results provide new potential therapeutic targets for blocking the progression of HCC induced by CXCL12-CXCR4 axis and CCL21-CCR7.